Management strategy influences landscape patterns of high-severity burn patches in the southwestern United States - Singleton, Megan P.; Thode, Andrea E.; Sánchez Meador, Andrew J.; Iniguez, Jose M.; Stevens, Jens T. (Landscape ecology, 2021)
Context Spatial patterns of high-severity wildfire in forests affect vegetation recovery pathways, watershed dynamics, and wildlife habitat across landscapes. Yet, less is known about contemporary trends in landscape patterns of high-severity burn patches or how differing federal fire management strategies have influenced such patterns. Objectives We assessed fires managed for ecological/resource benefit and fires that are fully suppressed and investigated: (1) whether spatial patterns of high-severity patches differed by management strategy, (2) whether spatial patterns were related to fire size and percent high-severity fire, and (3) temporal trends in spatial patterns. Methods We examined high-severity spatial patterns within large fires using satellite-derived burn severity data from 735 fires that burned from 1984 to 2017 in Arizona and New Mexico, USA. We calculated a suite of spatial pattern metrics for each individual fire and developed a method to identify those which best explained variation among fires. Results Compared to managed fires, spatial pattern metrics in suppression fires showed greater patch homogeneity. All spatial pattern metrics showed significant relationships with fire size and percent high-severity fire for both management strategies. Mean annual spatiotemporal trends in suppression fires have moved toward smaller, more complex, fragmented patches since the early 2000s. Conclusions Increases in fire size and proportion high-severity fire are driving more homogenous patches regardless of management type, with percent high-severity more strongly driving average temporal trends. Anticipated shifts in fire size and severity will likely result in larger, more contiguous, and simple-shaped patches of high-severity fire within southwestern conifer forests.